Memulihkan Komunikasi Belajar dari Jatuh Bangunnya Kabinet Pada Masa Demokrasi Parlementer - Mukti Diapepin (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
AbstractPolitical communication at this time, often hit by problems. Each elite expressed his sector ego - which ended in conflict. The same condition also happened during Parliamentary Democracy. The ups and downs of the cabinet - mainly triggered by communication bottlenecks that lead to a vote of no confidence. Each political opponent, trying to find weaknesses that lead to impeachment. New communica-tion can be interwoven during the Burhanuddin Harahap cabinet. This is evidenced by the success of the 1955 General Election. All political party leaders, trying to find common ground, to succeed in holding the first elections in Indonesia.